1997
DOI: 10.1097/00003246-199710000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress increases survival rates in lipopolysaccharide-stimulated rats

Abstract: We conclude that heat stress applied after the initiation of endotoxemia can provide protection against an otherwise lethal stimulus and that the mechanism of protection may be related to the attenuation of plasma IL-1 beta concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
74
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 35 publications
9
74
0
2
Order By: Relevance
“…This inhibitory effect may be related to stabilization of I B␣, possibly through the prevention of IKK activation. Taken together with protective effects of HSP induction in an in vivo animal model of ALI (13,14), the findings presented here suggest that HSP induction may be utilized a novel therapeutic modality in ALI.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This inhibitory effect may be related to stabilization of I B␣, possibly through the prevention of IKK activation. Taken together with protective effects of HSP induction in an in vivo animal model of ALI (13,14), the findings presented here suggest that HSP induction may be utilized a novel therapeutic modality in ALI.…”
Section: Discussionsupporting
confidence: 55%
“…Recently, RANTES and inducible NO synthase gene expressions were shown to be inhibited by prior HSP induction in human and murine lung epithelial cells, respectively (22,23). In addition to these in vitro studies, the protective effect of HSP induction was documented to be related to the attenuation of plasma IL-1␤ concentrations in an in vivo model of ALI (14). These findings suggest that one potential mechanism of protection may be the ability of HSPs to inhibit pro-inflammatory responses in lung cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, intracellular problems (spontaneous transcriptional and translational errors, sudden increase in protein synthesis or excess of synthesized subunits, incorrect cellular localization, or the damaging effect of highly reactive free radicals) as well as extracellular stressors (high temperature, hypoxia, radiation, toxic chemicals, endotoxins, and osmotic pressure) can alter the folding capacity of a cell leading to translational arrest as well as the accumulation of misfolded or unfolded proteins. [9][10][11][12][13][14] To insure protein homeostasis, cells employ several systems. These include intracellular removal or processing of misfolded proteins, 15 involving cellular chaperones, the ubiquitin-proteasome system, and autophagy.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…For example, heat-accelerated apoptosis could result in proinflammatory removal of apoptotic neutrophils, particularly when these apoptotic cells become opsonized with ANCAs (30)(31)(32). However, other investigators have found that, based on observations in animal and human studies, fever is beneficial in host defense reactions, and also that antipyretic treatment interferes with this effect (19)(20)(21)33).…”
mentioning
confidence: 99%